2013
DOI: 10.1111/jocn.12117
|View full text |Cite
|
Sign up to set email alerts
|

Community‐based postpartum exercise program

Abstract: It is worthwhile promoting a yoga and Pilates exercise programme for postpartum women in communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 29 publications
2
50
0
3
Order By: Relevance
“…(1,21,22) In our study, we found that Pilates home exercises were able to reduce postpartum maternal fatigue. The exercises were shown to reduce general, physical and mental fatigue, and improve activity and motivation.…”
Section: Discussionmentioning
confidence: 56%
“…(1,21,22) In our study, we found that Pilates home exercises were able to reduce postpartum maternal fatigue. The exercises were shown to reduce general, physical and mental fatigue, and improve activity and motivation.…”
Section: Discussionmentioning
confidence: 56%
“…A 60-minute, once a week exercise session for 3 months revealed a significant reduction in depression scores in those who were at a high risk for depression (P = 0.021). 13 Three years later, Buttner et al 29 performed a small randomized trial that supported Ko's findings. Twentyeight of 57 women at high risk for postpartum depression participated in yoga classes twice a week for 8 weeks.…”
Section: Postpartumsupporting
confidence: 51%
“…The characteristics of the included studies are summarized in Table , six were single‐arm interventions , seven were non‐RCTs and 33 were RCTs . Most studies were conducted in developed countries: Australia ( n = 6); USA ( n = 24); Taiwan ( n = 4); Canada ( n = 3); and Austria, Finland, Greece, Netherlands, Sweden, Japan and UK ( n = 1 for each country) (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…About half of the studies were at low risk of bias from missing outcome data and six of those conducted intention-to-treat analysis (26,28,29,65,78,80). Seven studies were at high risk of attrition bias due to unequal attrition across the intervention and control groups which could be related to the true outcome (34,40,52,61,70,71,81). All outcomes were reported as pre-specified in seven studies (21,28,35,36,43,52,82), suggesting low risk of bias from selective reporting.…”
Section: Quality Assessmentmentioning
confidence: 99%